Minimum 6-Year Follow-Up After Ulnar Nerve Decompression and Submuscular Transposition for Primary Entrapment - Zimmerman, Ryan M.; Jupiter, Jesse B.; González del Pino, Juan (The Journal of hand surgery (American ed.), 2013)
To retrospectively evaluate patients with 6-year minimum follow-up after submuscular transposition of the ulnar nerve for primary entrapment. From 1992 to 2005, 142 patients were treated surgically for ulnar neuropathy at the elbow by 2 senior surgeons using a technique that preserved nerve vascularity. A total of 99 cases were eligible, and 82 elbows in 76 patients, average age 48 years, were followed for at least 6 years (average, 8.3 y). Thirty-two (42%) were male, and the dominant limb was involved in 49 (64%). The average duration of symptoms before surgery was 25 months. Clinical records were reviewed, and sensory (S0–2) and motor (M0–5) testing was performed. Dellon scores were determined, and visual analog scale and modified questionnaires from Novak et al and Kleinman and Bishop were completed. Preoperatively, 48 elbows were Dellon grade III, 33 were grade II, and one was grade I. There were clinically and statistically significant improvements in patient and surgeon-reported data regardless of the preoperative disease severity. Visual analog scale questionnaires, sensory scale, and motor strength all improved, with at least antigravity strength in all subjects. Dellon scores also improved, and 38 elbows had normalized to Dellon 0. Of the 33 preoperative elbows that were grade III, 15 improved to grade II, 13 to grade I, and 5 normalized. Of the 48 preoperative elbows that were grade II, 16 improved to grade I and 32 normalized. Preoperative Dellon III elbows had more residual symptoms than grade II elbows. A total of 73 elbows (89%) had a good or excellent outcome. There were no reoperations or infections. Submuscular transposition is a safe and durable option for primary ulnar neuropathy at the elbow. Overall, good or excellent results were achieved in 89% of patients with a low complication rate. Therapeutic IV.